Learn and relearn “normality”. From human zoos to committted vignette (Anclajes, 2019)
Human beings have the habit of labeling everything and everyone. this is something that the recent emergence of social networks has taken to its fullest extent. If the established standards are not fulfilled, it will rain attacks on those who have dared to do or to say something that does not suit them. In this work we approach the queer into the field of contemporary Latin America comics, as a modern reflection of everything that is differentent and, therefore marginal, at a bodily, sexual and gender level.
Keywords: Education; Comic book; diversity; Queer